Pharmacokinetics of daridorexant, a dual orexin receptor antagonist, are not affected by renal impairment - Benjamin Berger; Clemens Muehlan; Gernot Klein; Jasper Dingemanse (Wiley, 2021)
Abstract The aim of this study was to evaluate the impact of renal impairment on the pharmacokinetics (PKs), safety, and tolerability of daridorexant, a dual orexin receptor antagonist intended for the treatment of insomnia. A single‐center, open‐label study evaluated the PKs of daridorexant in patients with severe renal function impairment (SRFI; determined by creatinine clearance using the Cockcroft‐Gault equation; N = 8) not on dialysis, and in matched control subjects (based on sex, age, and body weight; N = 7). A single oral dose of daridorexant 25 mg was orally administered in the morning. Blood samples were collected up to 72 h postdose for PK assessments of daridorexant. In patients with SRFI, maximum plasma concentrations (Cmax; geometric mean ratio [GMR] and 90% confidence interval [CI]: 0.94 [0.60-1.46]), time to reach Cmax (Tmax; median difference [90% CI] of −0.25 h [−0.75 to 0.25]), and half‐life (GMR [90% CI] of 0.99 [0.66-1.48]), were virtually unchanged. Exposure (area under the plasma concentration‐time profile) to daridorexant was slightly higher in patients with SRFI than in control subjects with the GMR (90% CI) being 1.16 (0.63-2.12). No safety issue of concern was detected as all adverse events were transient and of mild or moderate intensity, and no treatment‐related effects on vital signs, clinical laboratory, or electrocardiogram variables were observed following daridorexant administration in patients with SRFI and control subjects. Based on these observations, PK alterations of daridorexant due to renal function impairment are not considered of clinical relevance and no dose adjustment is necessary in these patients.